COMPETITIVENESS THROUGH THE INTEGRATION OF LOGISTICS ACTIVITIES IN SMEs - OMORUYI, Osayuwamen (Studia Universitatis Babeș-Bolyai Oeconomica, 2018)
Logistics among competing organisations is a strategic management activity that can affect the operational, market and financial performance of an organisation. Small and medium enterprises (SMEs) need to understand the role of logistics activities in achieving competitive performance and creating a high level of customer satisfaction through greater economies of scale in production and reduction in the price of goods. This study aims to determine the nature and extent of SMEs competitiveness through logistics activities. This research used a quantitative method of data collection and analysis. The data were statistically analysed using SPSS (25.0) as well as SMART-PLS (3.0) software for structural equation modelling (SEM) to assess the measurement reliability and the research structural model. The findings show that SMEs nature and extent of competitiveness based on logistics activities differs among the three measurement constructs, namely price/cost competitiveness, quality competitiveness and delivery competitiveness. This study adds value to the knowledge of the perceived benefits and importance of logistics activities among the participating SMEs. JEL classification: L1